Efetividade de ações de promoção do consumo de frutas e hortaliças no Programa Academia da Saúde - Raquel de Deus Mendonca (2016)
Inadequate fruit and vegetable (FV) consumption is related to high disease load worldwide, highlighting the need for intervention, effective, inexpensive and applicable.This study aimed to assess the effectiveness of a nutritional intervention based on trans-theoretical model, dialogic and problematizing pedagogy for increasing the FV consumption of users of the Program Academia da Saúde (PAS) of Belo Horizonte, Minas Gerais. This volume will be presented in four articles: 1) The dietary profile of socially vulnerable participants of health promotion programs ina Brazilian metropolis; 2) Promoting fruit and vegetable consumption: a randomized controlled community Trial; 3) Adherence to a community nutritional intervention and associated factors; and 4) Interventional promotion for consumption of fruits and vegetables in a primary healthcare service: A randomized controlled trial. Article 1 of the thesis has a cross-sectional design (n=370) and it aimed to identify the dietaryprofile of participants of two PAS units located in socially vulnerable areas, in addition to characterize the consumption of FH. The second study describes the design of the intervention, addressing the actions and educational strategies used. The articles 2 and 3 are parts of a randomized controlled trial in a community conducted in a representative sample, which consisted of 18 PAS poles. The third article calculatedadherence to a community nutritional intervention and its associated factors, and the fourth article assessed the effectiveness and process of an intervention to increase FV consumption. We found, in the first article, inadequate fruit consumption among users of PAS (67.7% pole I and 75.7% pole II), and users of the PAS pole in the most socially vulnerable area had higher vegetable intake inadequacy (43.6% vs. 54.6%; p=0.038). In view of these findings we were develop educational actions based on trans-theoretical model and dialogic and problematizing pedagogy. The actions took place over seven months and the educational strategies included: workshops, motivational messages conveyed via postcards, interactive environment-based activities, and informative material. After seven months 2,241 individuals wereevaluated, 1,305 in the control group (CG) and 936 intervention group (IG), most women (88.3% GC and 84.8% GI), older adults and low education level. Regarding the change stages of behavior for the consumption of FH, at baseline in GI, 15.6% of individuals were in pre-action, 26.9% preparation and 57.9% in action. The proposedcommunal intervention had an adherence rate of 58.3%, which was associated with higher age, being unemployed, not receiving treatment for psychiatric diseases, having body satisfaction, and frequenting PAS for more time (13 months or more). During the study period, there werent in CG and IG actions related to FH consumption, except from this study, but were offered 73 health actions at poles of the CG (880 participants, 49.6% coverage ) and 26 (600 participants, 55.6% coverage) in only six poles of the IG. The intervention of this study has offered 12 different actions at each pole of the IG, totaling 108 activities repeated at differenttimes (868 participants in at least two actions, with 92.7% coverage). The participants of IG in the lowest quartile of FH consumption increased intake of these foods ( = 27,5g, 95% CI: 6.4, 48.6) compared to CG, in addition, in the IG reporting increased self-efficacy (p<0.001), reduced perceived barriers to FH consumption (p= 0.003) and significant progression to the action stage (57.2% to 70.1%; p <0.001). PAS newusers had inappropriate dietary profiles compatible with the development of chronic diseases, suggesting the importance of actions health promotion, such as that encourage FV consumption. These findings indicate that nutritional intervention promoted the consumption of FV, especially among those who had a lower intake, and increased self-efficacy and reduced the perception of barriers for the consumption of FV. Moreover, the intervention nutritional has high adherence rates,showing that PAS is a differentiated place for its realization, however, strategies need to be developed to increase adherence among younger and employed individuals, individuals dissatisfied with their body weight, and individuals with lower PAS attendance. We concluded that, conducting nutrition intervention in primary care, theoretically structured, was a useful strategy to improve and maintain the adequate intake of FH.